Risk factors and outcomes of intraoperative hypothermia in neonatal and infant patients undergoing general anesthesia and surgery - Jialian Zhao; Zhenkai Le; Lihua Chu; Yi Gao; Manqing Zhang; Jiabin Fan; Daqing Ma; Yaoqin Hu; Dengming Lai (Frontiers Media S.A., 2023)
ObjectiveThe incidence of intraoperative hypothermia remains high in pediatric patients during anesthesia and surgery even though core body temperature monitoring and warming systems have been greatly improved in recent years. We analyzed the risk factors and outcomes of intraoperative hypothermia in neonates and infants undergoing general anesthesia and surgery.MethodsThe data on the incidence of intraoperative hypothermia, other clinical characteristics, and outcomes from electronic records of 1,091 patients (501 neonates and 590 infants between 28 days and 1 year old), who received general anesthesia and surgery, were harvested and analyzed. Intraoperative hypothermia was defined as a core temperature below 36°C during surgery.ResultsThe incidence of intraoperative hypothermia in neonates was 82.83%, which was extremely higher than in infants (38.31%, p < 0.001)-the same as the lowest body temperature (35.05 ± 0.69°C vs. 35.40 ± 0.68°C, p < 0.001) and the hypothermia duration (86.6 ± 44.5 min vs. 75.0 ± 52.4 min, p < 0.001). Intraoperative hypothermia was associated with prolonged PACU, ICU, hospital stay, postoperative bleeding, and transfusion in either age group. Intraoperative hypothermia in infants was also related to prolonged postoperative extubation time and surgical site infection. After univariate and multivariate analyses, the age (OR = 0.902, p < 0.001), weight (OR = 0.480, p = 0.013), prematurity (OR = 2.793, p = 0.036), surgery time of more than 60 min (OR = 3.743, p < 0.001), prewarming (OR = 0.081, p < 0.001), received >20 mL/kg fluid (OR = 2.938, p = 0.004), and emergency surgery (OR = 2.142, p = 0.019) were associated with hypothermia in neonates. Similar to neonates, age (OR = 0.991, p < 0.001), weight (OR = 0.783, p = 0.019), surgery time >60 min (OR = 2.140, p = 0.017), pre-warming (OR = 0.017, p < 0.001), and receive >20 mL/kg fluid (OR = 3.074, p = 0.001) were relevant factors to intraoperative hypothermia in infants along with the ASA grade (OR = 4.135, p < 0.001).ConclusionThe incidence of intraoperative hypothermia was still high, especially in neonates, with a few detrimental complications. Neonates and infants each have their different risk factors associated with intraoperative hypothermia, but younger age, lower weight, longer surgery time, received more fluid, and no prewarming management were the common risk factors.